Response of epiphytic bryophytes to simulated N deposition in a subtropical montane cloud forest in southwestern China - Song, L.; Liu, Wen-Yao; Ma, W.; Qi, J. (Springer-Verlag, 2012)
A field manipulation experiment was conducted in a subtropical montane cloud forest in southwestern China to determine the possible responses of epiphytic bryophytes to increasing nitrogen (N) deposition from community to physiology level, and to find sensitive epiphytic bryophytes that may be used as indicators for assessing the degree of N pollution. N addition had significantly negative effects on species richness and cover of the epiphytic bryophyte community. Harmful effects of high N loads were recorded for chlorophyll, growth, and vitality of the species tested. The decline of some epiphytic bryophytes may result from detrimental effects on degradation to photosynthetic pigments. Bazzania himalayana (Mitt.) Schiffn., Bazzania ovistipula (Steph.) Mizut., and Homaliodendron flabellatum (Sm.) Fleisch. are candidates in atmospheric nitrogen monitoring. Epiphytic bryophytes in the montane cloud forest are very sensitive to increasing N deposition and often difficult to recover once they have been destroyed, providing early detection of enhanced N pollution for trees or even the whole forest ecosystem. The inference that increasing N pollution may lead to loss of biodiversity is a concern to the developing economy in western China, and should alert the government to the adverse impacts caused by increased industrial pollution during the process of China’s West Development.